2010
DOI: 10.1002/jmri.22101
|View full text |Cite
|
Sign up to set email alerts
|

Human cervical spinal cord funiculi: Investigation with magnetic resonance diffusion tensor imaging

Abstract: Purpose: To use spinal cord diffusion tensor imaging (DTI) for investigating human cervical funiculi, acquire axial diffusion magnetic resonance imaging (MRI) data with an in-plane resolution sufficient to delineate subquadrants within the spinal cord, obtain corresponding DTI metrics, and assess potential regional differences. Materials and Methods:Healthy volunteers were studied with a 3 T Siemens Trio MRI scanner. DTI data were acquired using a single-shot spin echo EPI sequence. The spatial resolution allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
5
19
1
Order By: Relevance
“…We observed that the FA and ADC values indicated significant differences between GM and individual WM funiculi. These data are supported by previous studies [1,21]. In addition, we found that there were significant differences in the FA and ADC values of the different WM funiculi at different CSC segments, but that there were no differences in the DTI parameters of the GM from different CSC segments, an analysis that was not performed by Vedantam et al Compared with the upper and middle segments, both FA and ADC values from WM funiculis of lower segments were lower.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We observed that the FA and ADC values indicated significant differences between GM and individual WM funiculi. These data are supported by previous studies [1,21]. In addition, we found that there were significant differences in the FA and ADC values of the different WM funiculi at different CSC segments, but that there were no differences in the DTI parameters of the GM from different CSC segments, an analysis that was not performed by Vedantam et al Compared with the upper and middle segments, both FA and ADC values from WM funiculis of lower segments were lower.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we found that there were significant differences in the FA and ADC values of the different WM funiculi at different CSC segments, but that there were no differences in the DTI parameters of the GM from different CSC segments, an analysis that was not performed by Vedantam et al Compared with the upper and middle segments, both FA and ADC values from WM funiculis of lower segments were lower. These results could be due to the decreased spinal cord volume of the lower segments, or to differences in signal-to-noise ratio (SNR) across the cervical segments [1,11,21].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations